PENGAMBILAN KEPUTUSAN SISWA DALAM MEMBUAT PENGAJUAN MASALAH MATEMATIKA BERDASARKAN IDE KREATIF SCAMPER PADA MATERI UKURAN PEMUSATAN DATA - Klara Angellia; Muchtadi Muchtadi; Jamilah Jamilah (Journal of Educational Review and Research, 2022)
This research is a descriptive qualitative type in the form of a case study. The purpose of this study is that researchers want to see the extent to which students' decision making in making mathematical problem submissions based on SCAMPER's creative ideas. SCAMPER stands for substitute, combine, adapt, modify, put to other uses, eliminate, rearrange/reverse. This research was conducted at SMP Negeri 5 Manyuke with the research subjects being 27 students of class VIII (eight). Data collection techniques used are measurement techniques and direct communication techniques in the form of interviews. The measurement technique here is the researcher gives a test in the form of a student work sheet as a data collection tool and the interviews conducted by the researcher are semi-structured interviews using interview guidelines as a data collection tool. The results of the research that the researchers found were that students' decision making in making problem submissions based on SCAMPER's creative ideas on the size of the data concentration material in general was quite good. In addition, from 27 students there are 6 students who have high abilities, 18 students who have moderate abilities, and 3 students who have low abilities. Of the three levels of student ability, namely high, medium, and low for decision making in making mathematical problem submissions on data centering material, it can be said to be very good for high abilities, good enough for moderate abilities, and very poor for low abilities.